EVALUATION OF THE SUPPLEMENTARY FEEDING PROGRAM FOR TODDLERS - Suci Rahmadani; Mattaliu, Salsabila Dwi Qalbi; Nazaruddin, Balqis (Homes Journal = Hospital Management Studies Journal, 2023)
Background: Malnutrition in children under five is still a matter of concern because it not only harms the child, but also harms the country. Malnourished toddlers if not treated properly can have an impact until adulthood. Objective: This study aims to evaluate the Supplementary Feeding Program (PMT) for toddlers at Puskesmas Somba Opu, Gowa Regency. Methods: The research method used was a cross sectional design with a quantitative approach. The population in this study were mothers who had toddlers and followed the PMT program at Puskesmas Somba Opu as many as 135 people. The sampling technique used proportionate stratified random sampling technique. The research was conducted at the Somba Opu Health Center in January-June 2023. Data analysis techniques used were univariate and bivariate using the Fisher test and contingency coefficient. Results: the input aspect for the funding component is still lacking. The process aspect of the recording component is still lacking. The output aspect is said to be sufficient in maternal attitudes and the coverage of Supplementary Feeding performance. There was a relationship between process and maternal attitude (p=0.000). Conclusion: the funding and recording components are still lacking and there is a relationship between the process and the mother's attitude in the implementation of the Supplementary Feeding program at Puskesmas Somba Opu, Gowa Regency. It is recommended to provide funds for the implementation of the PMT program for toddlers in the working area of Puskesmas Somba Opu, Gowa Regency